Six new species of Tetra Keifer (Acari: Eriophyidae: Phyllocoptinae) from China - Xue, Xiao-Feng; Song, Zi-Wei; Hong, Xiao-Yue (Zootaxa, 2007)
In this paper, six new species of Tetra Keifer from China are described and illustrated, namely Tetra actinidiae sp. nov. on Actinidia sp. Lindl. (Actinidiaceae); Tetra coriariae sp. nov. on Coriaria nepalensis Wall. (Coriariaceae); Tetra diamantiacae sp. nov. on Rhamnus diamantiaca Nakai (Rhamnaceae); Tetra hupeanae sp. nov. on Dalbergia hupeana Hance (Leguminosae); Tetra sinicusis sp. nov. on Dipentodon sinicus Dunn (Celastraceae); Tetra zhouzhis sp. nov. on Pistacia chinensis Bunge (Anacardiaceae). A key to the species of Tetra in China is provided. The eriophyoid mite species described here are vagrants on leaf surfaces.